The Development of Indonesian Language Teaching Materials for Class VII Semester 1 Based on North Sumatran Local Wisdom and the Digitization of Learning - Syamsul Arif; Tangson R. Pangaribuan; Rosdiana Siregar; Ahmad Nur Cahyo; Siti Nurjanah; Rolando Napitupulu (BIRCU, 2021)
This study aims to develop teaching materials for Indonesian class VII SMP in semester 1 based on local wisdom of North Sumatra and the digitization of learning. The teaching materials that will be developed are descriptive text, narrative story text, and procedure text. This study uses the Research & Development method referring to the research design with the stages of analyzing the needs of teaching materials based on local wisdom, data collection, product design, validation and testing. Product assessment is based on material quality, language quality, and media quality, as well as testing as student responses. The results of the research show that: (1) the results of the validation of the material experts indicate that the learning materials are declared feasible and